Pengaruh Pemberian MP-ASI terhadap Tingkat Morbiditas Anak di Indonesia (Analisis Data SDKI Tahun 2017) - Nurhalina Nurhalina; Dwi Purbayanti; Rinny Ardina; Muhammad Fitriyanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The results of the 2017 IDHS show that the level of child morbidity in Indonesia is still quite high with the main symptoms found are ARI, diarrhea, and fever. Meanwhile, 43% of infants do not get breast milk, 48% do not get exclusive breastfeeding and 60% of children receive food not in accordance with WHO recommendations. The purpose of this study was to determine the effect of feeding patterns on the level of child morbidity in Indonesia by analyzing the IDHS data in 2017. The method was a cross-sectional study. The population was women of childbearing age realized in the 2017 IDHS and sample who had children aged ≤ 2 years and having sick during the survey period. The sample was excluded if the children had died or lived with other people and had a history of birth weight <2500 gram. Data analysis using chi-square test and multivariate analysis with logistic regression. The results showed that the pattern of giving complimentary food (p-value = 0.033 and OR=1.214) influenced the level of child morbidity in Indonesia.